The study of effect of the altitude training before competitiion on athletes' self-organization in aspect of nerve-biology - Lin, L.; Li, J. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
This study examined the effect of the altitude training before competitiion on athletes' self-organization in aspect of nerve-biology and showed 1) First, altitude training can't replace the specially designed training before match. The duration of effect of altitude training depends on the training plan before match and scheme in intensity during altitude training. 2) Second, all the indexes of brain function, such as information entropy dispersing?dominant oscillatory level of information entropy dispersing or shift to right, have indicated descent of athletes' sport ability. The ordinary index in biochemistry and physiology, such as Hb, urea nitrogen in serum (Bun) etc, can only reflect ordinary function of athletes' organism. They have no linear relationship with athletes' sport ability.